Decoding the Structure of Non-Proteinogenic Amino Acids: The Rotational Spectrum of Jet-Cooled Laser-Ablated Thioproline - Juan Carlos López; Alberto Macario; Andrés Verde; Alfonso Pérez-Encabo; Susana Blanco (Molecules, 2021)
The broadband rotational spectrum of jet-cooled laser-ablated thioproline was recorded. Two conformers of this system were observed and identified with the help of DFT and ab initio computations by comparison of the observed and calculated rotational constants and 14N quadrupole coupling constants as well as the predicted energies compared to the observed relative populations. These conformers showed a mixed bent/twisted arrangement of the five-membered ring similar to that of the related compound thiazolidine with the N–H bond in axial configuration. The most stable form had the COOH group in an equatorial position on the same side of the ring as N-H. The arrangement of the C=O group close to the N-H bond led to a weak interaction between them (classified as type I) characterized by a noncovalent interaction analysis. The second form had a trans-COOH arrangement showing a type II O–H···N hydrogen bond. In thioproline, the stability of conformers of type I and type II was reversed with respect to proline. We show how the conformation of the ring depends on the function associated with the endocyclic N atom when comparing the structures of isolated thioproline with its zwitterion observed in condensed phases and with peptide forms.